Luteal blood flow as a predictive factor for methotrexate treatment outcomes in women with unruptured tubal pregnancy - Li Wang; Meili Pei; Ting Yang; Juan Zhao; Xiaofeng Yang (BMC, 2020)
Abstract Background Blood flow in the corpus luteum is associated with luteal function. However, the impact of luteal blood flow on methotrexate (MTX) treatment in women with unruptured tubal pregnancy has not been reported. The aim of the present study was to observe the impact of luteal blood flow on the therapeutic effect of MTX in women with unruptured tubal pregnancy. Methods A prospective observational study recruited 129 women with unruptured tubal pregnancy in the First Affiliated Hospital of Xi'an Jiaotong University from September 2016 to June 2018. One hundred and fifteen women were treated successfully with MTX, and women were divided into 2 groups according to luteal blood flow: the poor luteal blood flow group and the abundant luteal blood flow group. The therapeutic effects were compared between the two groups. Results Women in the abundant luteal blood flow group had a significantly higher serum β-human chorionic gonadotropin (β-hCG) level 4 days, 1 week and 2 weeks after MTX treatment compared with women in the poor luteal blood flow group (P < 0.05). The average diameter of the ectopic mass 1 week, 2 weeks and 3 weeks after MTX treatment in women with abundant luteal blood flow was significantly larger (P < 0.05), and the time of serum β-hCG clearance and ectopic mass disappearance were significantly longer compared with those in women in the poor luteal blood flow group (P < 0.05). Conclusions Luteal blood flow might be a predictive factor for MTX treatment outcomes in women with unruptured tubal pregnancy, and those with abundant luteal blood flow need a longer recovery time.